2012
DOI: 10.1002/lary.22496
|View full text |Cite
|
Sign up to set email alerts
|

3 Tesla turbo‐FLASH magnetic resonance imaging of deglutition

Abstract: MRI of swallowing using the described technique is reliable and provides a unique evaluation of the swallowing sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Utilizing this technology, we were able to produce excellent image quality with a temporal resolution of 113 ms, with good visualization of the tongue base and pharyngeal constrictors during swallowing in axial planes. 19 In the current study, we expand on our previous work by demonstrating the inherent feasibility and reliability of the technique to characterize pharyngeal and UES movements in normal, healthy adults. Our data demonstrate that spatial and temporal measurements of pharyngeal wall movement can be reliably performed and show a definable pattern at both the C2 and UES levels.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Utilizing this technology, we were able to produce excellent image quality with a temporal resolution of 113 ms, with good visualization of the tongue base and pharyngeal constrictors during swallowing in axial planes. 19 In the current study, we expand on our previous work by demonstrating the inherent feasibility and reliability of the technique to characterize pharyngeal and UES movements in normal, healthy adults. Our data demonstrate that spatial and temporal measurements of pharyngeal wall movement can be reliably performed and show a definable pattern at both the C2 and UES levels.…”
Section: Discussionmentioning
confidence: 80%
“…Utilizing this technology, we were able to produce excellent image quality with a temporal resolution of 110ms, with good visualization of the tongue base and pharyngeal constrictors during swallowing in the axial and sagittal planes. (19)…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously described dynamic magnetic resonance imaging (dMRI) as a technique that allows examination of the swallow sequence with improved visualization of these structures in the axial plane during normal swallow in healthy patients. 11,12 Further study demonstrated good intraexaminer and interexaminer reliability for measurements of the pharyngeal area. 13 Although a limitation of dMRI includes supine positioning and a theoretically increased risk of aspiration, studies have shown that bolus transport to the UES and timing of muscle activation are not changed by the supine position.…”
Section: Introductionmentioning
confidence: 81%
“…The study could not differentiate patient subgroups with PD stages (H&Y 1, 1.5, 2 and 2.5) or patients with and without dysphagia risk-signs. Dynamic MRI constraints in swallowing assessment are: (a) supine position in some cases, it may be awkward or unnatural position for water-intake (b) it may not fully represent actual situation, though it has been reported as noninterfering with assessment 28,53,54 ; (c) may not be feasible in medically unstable, disoriented, or uncooperative patients like VFS and FEES; (d) objectifying the overlapping phases of swallowing; (e) patients with MRI contraindications cannot be evaluated.…”
Section: Discussionmentioning
confidence: 99%